Design, semisynthesis and potent cytotoxic activity of novel 10-fluorocamptothecin derivatives - Yang, Cheng-Jie (Bioorg Med Chem Lett, 2017)
Fluorination is a well-known strategy for improving the bioavailability of bioactive molecules in the lead optimization phase of drug discovery projects. In an attempt to improve the antitumor activity of camptothecins (CPTs), novel 10-fluoro-CPT derivatives were designed, synthesized and evaluated for cytotoxicity against five human cancer cell lines (A-549, MDA-MB-231, KB, KB-VIN and MCF-7). All of the derivatives showed more potent in vitro cytotoxic activity than the clinical CPT-derived drug irinotecan against the tumor cell lines tested, and most of them showed comparable or superior potency to topotecan. Remarkably, compounds 16b (IC(50), 67.0 nM) and 19b (IC(50), 99.2 nM) displayed the highest cytotoxicity against the multidrug-resistant (MDR) KB-VIN cell line and merit further development as preclinical drug candidates for treating cancer, including MDR phenotype. Our study suggested that incorporation of a fluorine atom into position 10 of CPT is an effective method for discovering new potent CPT derivatives.